The Role of Hypoxic Mesenchymal Stem Cells Conditioned Medium in Increasing Vascular Endothelial Growth Factors (VEGF) Levels and Collagen Synthesis to Accelerate Wound Healing - Sunarto, Hadi; Trisnadi, Setyo; Putra, Agung; Sa'dyah, Nur Anna Chalimah; Tjipta, Arya; Chodidjah, Chodidjah (Indonesian Journal of Cancer Chemoprevention, 2020)
Full-thickness wound are areas damage of skin associated with loss of epidermis and dermis. The wound healing mechanism consists proliferation, migration and remodeling. Hypoxic conditional medium of mesenchymal stem cells (HMSCs-CM) contains lots of soluble molecules, such as protein growth factor and cytokine anti-inflammation. The soluble molecule of HMSCs-CM plays a critical role in wound healing by upregulation of VEGF and collagen synthesis. The objective of this study was to evaluate the effect of HMSCs-CM on VEGF and collagen concentrations in rats with incised wounds. The methods of this study were an experimental animal study with post-test only control group design was performed involving 24 Wistar rats. The rats were randomized into four groups consisting of sham, control and two treatment groups (gel of HMSCs-CM at doses of 200 μL and 400 μL). The VEGF levels and collagen density were analyses using ELISA assay and Masson-trichome specific staining, respectively. One-way ANOVA and Post Hoc LSD were used to analyses the data. The results of this study showed that a VEGF levels was significant increased on day 6 with doses-dependent manner. Interestingly, the VEGF levels gradual decrease on day 9. In addition, the decreased of VEGF levels on day 9 in this study in line with our findings in which we found there was a trend in the decreased of collagen density, it indicated the completion of remodeling phase and there has been an acceleration in wound healing. This study demonstrated that HMSCs-CM were able to regulate VEGF levels and collagen synthesis in accelerate wound healing. The role of HMSCs-CM stimulate cutaneous wound healing should be clarified further.Keywords: hypoxic conditional medium of mesenchymal stem cells (HMSCs-CM), vascular endothelial growth factor, collagen synthesis, paracrine factors